Fresno County Women Lawyers Annual Dinner: Honoring Mary Louise Frampton - Watkins, Howard::::::::: (1989)
Retired Justice George Brown, retired Judge Harold Thompson, Deputy DA Vincent McGraw, Justice Hollis Best and 2nd District Court of Appeal Presiding Justice Arleigh Woods